Microbiologically Contaminated and Over-Preserved Cosmetic Products According Rapex 2008–2014 - Edlira Neza; Marisanna Centini (Cosmetics, 2016)
We investigated the Rapid Alert System (RAPEX) database from January 2008 until week 26 of 2014 to give information to consumers about microbiologically contaminated cosmetics and over-preserved cosmetic products. Chemical risk was the leading cause of the recalls (87.47%). Sixty-two cosmetic products (11.76%) were recalled because they were contaminated with pathogenic or potentially pathogenic microorganisms. Pseudomonas aeruginosa was the most frequently found microorganism. Other microorganisms found were: Mesophilic aerobic microorganisms, Staphylococcus aureus, Candida albicans, Enterococcus spp., Enterobacter cloacae, Enterococcus faecium, Enterobacter gergoviae, Rhizobium radiobacter, Burkholderia cepacia, Serratia marcescens, Achromabacter xylosoxidans, Klebsiella oxytoca, Bacillus firmus, Pantoea agglomerans, Pseudomonas putida, Klebsiella pneumoniae and Citrobacter freundii. Nine cosmetic products were recalled because they contained methylisothiazolinone (0.025%–0.36%), benzalkonium chloride (1%), triclosan (0.4%) in concentrations higher than the limits allowed by European Regulation 1223/2009. Fifteen products were recalled for the presence of methyldibromo glutaronitrile, a preservative banned for use in cosmetics. Thirty-two hair treatment products were recalled because they contained high concentrations of formaldehyde (0.3%–25%).